Surfwise : the amazing true odyssey of the Paskowitz family [videorecording (DVD)] - Pray, Doug; Carter, Graydon (Magnolia Home Entertainment, 2008)
A look at the life of legendary Malibu surfer Dorian 'Doc' Paskowitz, a successful doctor who dropped out of normal society in the '60s and raised nine kids in a motor home, where he home-schooled them about life, love, sex, and surfing.